The Role of the Neurotrophin Network in Skin Squamous Cell Cancer and the Novel Use of the Zebrafish System - Marika Quadri; Elisabetta Palazzo (Elsevier, 2024)
Cutaneous squamous cell carcinoma (cSCC) is the second most prevalent form of skin cancer. An increasing number of cSCCs are associated with dysregulation of key molecules that control skin homeostasis. These observations have increased interest in the role of neurotrophins and their receptors in the pathogenesis of cSCC. They have been demonstrated to have a considerable impact on the aggressiveness potential of skin cancer by both in vitro and in vivo models. In this context, mouse models are classically used to dissect proliferation versus differentiation balance, but they have some limitations in terms of time, space, and costs. Recently, zebrafish models have been implemented as a new tool to obtain information regarding the invasive capacity and metastasis of neoplastic cells. By xenotransplantation technique, cSCC cells from a patient's biopsy or cell line can be successfully characterized, with or without the presence of genetic manipulation or treatments. In addition, the evaluation of the immune microenvironment contributes to potentially identifying connections and homologies with humans. In this review, we retrace the role of the neurotrophin network in healthy and pathological skin, particularly in cSCC. We review how zebrafish models can be important tools for studying cSCC development, growth, and potential treatments.